Variable Speed DC Generator Voltage Control using a Multistage Comparator - Augustinus Sujono; Feri Adriyanto; Hari Maghfiroh; Joko Slamet Saputro; Agus Ramelan (Universitas Sebelas Maret (UNS), 2021)
DC generator with variable rotation will produce uncontrolled voltage, causing problems in its utilization. In this study, it is proposed to develop a voltage control on the generator, in order to produce a fairly controllable and reliable voltage, with an analog circuit using a multistage comparator. Control of the generator output voltage is carried out by adjusting the field current from a separate voltage source which is forwarded to the resistance which is regulated based on the generator output voltage level with a multilevel comparison system. The results obtained are the output voltage ranges from 26 to 30 Volts and the output current ranges from 3 to 20 Amperes. This provides operational safety for the generator and battery. This technology can be used in dc generator systems in automotive engines, windmills, and other power plants.